Prenatal diagnosis in a fetuses with a clenched hands, overlapping fingers, and clubfoot due to MED12 deficiency in three affected siblings: A case report - Huiqin Xue; Qiaoyin Tang; Yu Feng; Chenyue Zhao; Ke Xu; Weiyue Gu; Zhaoyu Xue; Xinyan Li; Jinsong Jiang; Hongyong Lu; Xiayu Sun; Jianrui Wu; et al. (Frontiers in Genetics, 2023)
A fetal clenched hand with overlapping fingers is more common in aneuploidy syndrome and was not well-documented in MED12 deficiency. This study reports the clinical and genetic findings of three affected siblings from a Chinese family. The chromosome karyotype analysis diagram shows that karyotypes of the three children were normal. Trio whole-exome sequencing and Sanger sequencing verification found that there was a MED12 R296Q variant in normal mothers and their two offspring. A pattern of clenched hand with overlapping fingers (clinodactyly) and clubfoot was found in all the three affected siblings by three-dimensional ultrasound. The discovery of this case shows that even if the chromosome karyotype is normal, comprehensive prenatal genetic diagnosis is required when the ultrasound results show a clenched hand with clinodactyly and clubfoot symptoms.